Electrocatalytic and stoichiometric reactivity of 2D layered siloxene for high‐energy‐dense lithium–sulfur batteries. Issue 6 (30th September 2021) - Kang, Hui‐Ju; Park, Jae‐Woo; Hwang, Hyun Jin; Kim, Heejin; Jang, Kwang‐Suk; Ji, Xiulei; Kim, Hae Jin; Im, Won Bin; Jun, Young‐Si
Abstract: Lithium–sulfur batteries (LSBs) have emerged as promising power sources for high‐performance devices such as electric vehicles. However, the poor energy density of LSBs owing to polysulfide shuttling and passivation has limited their further market penetration. To mitigate this challenge, two‐dimensional (2D) siloxene (2DSi), a Si‐based analog of graphene, is utilized as an additive for sulfur cathodes. The 2DSi is fabricated on a large scale by simple solvent extraction of calcium disilicide to form a thin‐layered structure of Si planes functionalized with vertically aligned hydroxyl groups in the 2DSi. The stoichiometric reaction of 2DSi with polysulfides generates a thiosulfate redox mediator, secures the intercalation pathway, and reveals Lewis acidic sites within the siloxene galleries. The 2DSi utilizes the corresponding in‐situ‐formed electrocatalyst, the 2D confinement effect of the layered structure, and the surface affinity based on Lewis acid–base interaction to improve the energy density of 2DSi‐based LSB cells. Combined with the commercial carbon‐based current collector, 2DSi‐based LSB cells achieve a volumetric energy density of 612 Wh Lcell −1 at 1 mA cm −2 with minor degradation of 0.17% per cycle, which rivals those of state‐of‐the‐art LSBs. This study presents a method for the industrial production of high‐energy‐dense LSBs. Abstract : The electrocatalytic and stoichiometric reactivity of Si‐based materials toward polysulfides is investigated in high‐sulfur‐loading cathodes. The layered siloxene leads to redox‐mediating inorganic crystals, Lewis acidic Si sites, and two‐dimensional galleries for polysulfides via a chemical reaction, suppressing polysulfide shuttling more efficiently under sulfur‐loading conditions and thereby significantly improving the energy density of lithium–sulfur batteries.